2007
DOI: 10.1111/j.1365-2672.2007.03501.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification and characterization of an antifungal molecule produced by Bacillus licheniformis BC98, and its effect on phytopathogen Magnaporthe grisea

Abstract: Aims:  Isolation of bacterial antagonist for use in the biological control of phytopathogenic fungi like rice blast fungus, Magnaporthe grisea, and to further purify and characterize the antifungal molecule produced by the antagonist. Methods and Results:  Bacterial antagonist exhibiting highest antifungal activity against the rice blast fungus M. grisea was isolated from soil and identified as Bacillus licheniformis BC98. Besides M. grisea, the isolate also inhibited the growth of other phytopathogens such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 41 publications
(35 reference statements)
4
79
0
3
Order By: Relevance
“…In this way, decreased or delayed germination of sclerotia, achieved using this rhizobacteria collection, could be useful to reduce primary pathogen inoculum as noted with the lipopeptides producing B. amyloliquefaciens strains [13]. Similar effects have been reported by other authors on phytopathogenic fungi, suggesting that biosurfactant lipopeptides can traverse the fungal cell wall and induce serious alterations in plasma membrane permeability of active and resting structures [56,57].…”
Section: Discussionsupporting
confidence: 59%
“…In this way, decreased or delayed germination of sclerotia, achieved using this rhizobacteria collection, could be useful to reduce primary pathogen inoculum as noted with the lipopeptides producing B. amyloliquefaciens strains [13]. Similar effects have been reported by other authors on phytopathogenic fungi, suggesting that biosurfactant lipopeptides can traverse the fungal cell wall and induce serious alterations in plasma membrane permeability of active and resting structures [56,57].…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, Mejri et al (2017) demonstrated the lack of direct antifungal activity of surfactin against the pathogen Z. tritici in both in vitro and in planta bioassays [37]. Actually, the fungitoxic effects of surfactin have never been reported [12,13] except in the work of Tendulkar et al (2007) on rice. They showed that surfactin extracted from Bacillus licheniformis BC98 exhibited an in vitro direct fungicidal activity against the rice blast disease Magnaporthe grisea [40].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the fungitoxic effects of surfactin have never been reported [12,13] except in the work of Tendulkar et al (2007) on rice. They showed that surfactin extracted from Bacillus licheniformis BC98 exhibited an in vitro direct fungicidal activity against the rice blast disease Magnaporthe grisea [40]. Taken together, the findings of greenhouse trials and in vitro biocidal assays of the present study confirm that surfactin likely protects wheat against Z. tritici by inducing plant resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of pores further causes an increased Ca 2+ influx which has been reported to induce excessive branching of hyphae (Thrane et al, 1999;Mortel et al, 2009). The appearance of bulbous morphology may also be attributed to the effect of APB on the cytoskeletal elements, actin and tubulin leading to collapsed cytoskeleton and un-polarized growth at the tip of hyphae (Tendulkar et al, 2007). The other cellular responses observed in bioautographs viz.…”
Section: Discussionmentioning
confidence: 99%
“…lipopeptides, glycolipids, phospholipids, neutral lipids, polysaccharide-protein complexes and fatty acids produced by different bacterial isolates (El-Ghaouth, 1997;Szczech & Shoda, 2006;Romero et al, 2007, Tendulkar et al, 2007. The present study was taken up to isolate and screen the unexplored bacterial diversity of this region for its antifungal potential so as to develop biocontrol strategies as an alternative to chemical fungicides.…”
Section: Analysis Of Apb By Thin Layer Chromatography (Tlc) and High mentioning
confidence: 99%